Revisiting the democratic traditions in the South African trade union movement - Buhlungu, Sakhela (University of the Witwatersrand. History Workshop., 1999)
The Democratic traditions within South African trade unions have altered since 1994. They have become more oligarchic. The traditions of member participation, worker control and leadership accountability are discussed and how they have changed. The democratic tradition persists but is a matter of contestation.
Paper presented at the Wits History Workshop: Forging the links between historical research and the policy process, 18-19 September 1999.
Keywords: Trade Unions. South Africa; Democracy and Trade Unions